Rekrutacja i selekcja jako elementy procesu poszukiwania pracy w opinii pracobiorców - Połomski, Janusz (My University, 2012)
Aby znaleźć odpowiednią osobę na dane stanowisko pracodawcy dysponują szerokim wachlarzem metod i narzędzi. Mają one pomóc w wyłonieniu najlepszego ze wszystkich kandydatów. Rekrutacja i selekcja stały się istotnymi elementami zarządzania zasobami ludzkimi we współczesnych przedsiębiorstwach. Jest to ściśle związane z wysokimi kosztami prowadzania firm i rotacji pracowników. Osoby poszukujące pracy również uświadamiają sobie znaczenie metod rekrutacji i wyboru pracowników na wolne stanowiska w firmach. Poszukując pracy korzystają z różnorodnych sposobów dotarcia do informacji o wakatach. Ludzie chętnie i efektywnie wykorzystują Internet i prasę w poszukiwaniu pracy. W niniejszej pracy wskazano narzędzia wykorzystywane w rekrutacji pracowników oraz metody wyboru odpowiednich pracowników na wolne stanowiska pracy. Natomiast osoby poszukujące pracy by dotrzeć do potencjalnych pracodawców wykorzystują Internet, prasę oraz kontakty z rodziną i znajomymi.

To be able to find the right person for the job the employer has a wide range of methods and tools. Their aim is to help in identifying the best of all candidates. Recruitment and selection have become important elements of human resource management in modern enterprises. This is closely related to the high costs of conducting business and employee turnover. Job seekers also realize the importance of methods of recruitment and selection of employees for vacant positions in companies. When they are looking for work, they can use a variety of ways to find information about vacancies they are interest about. People willingly and effectively use the Internet and newspapers to search for a job. In this thesis, there are indicated tools used in recruitment and also selection methods to find employee best suitable for vacant jobs. Whereas job seekers to reach potential employers are using the Internet, newspapers and contact with family and friends.
Recruitment and selection as part of the process of finding work in the opinion of employers
Keywords: rekrutacja; selekcja pracowników; bezrobocie; praca; poszukiwanie pracy; recruitment; selection of workers; unemployment; job; job search